Academic health science networks' experiences with rapid implementation practice during the COVID-19 pandemic in England - Ziemann, Alexandra; Sibley, Andrew; Scarbrough, Harry; Tuvey, Sam; Robens, Sarah (Frontiers in Health Services, 2022)
The COVID-19 pandemic offered a “natural laboratory” to learn about rapid implementation of health and social care innovations in an altered implementation context. Our aim was to explore implementation practice of Academic Health Science Networks (AHSN) in the English National Health System during the first wave of the COVID-19 pandemic through a rapid implementation lens. We organized three 90-min, online, semi-structured focus groups with 26 operational and senior managerial staff from 14 AHSNs in June-July 2020. Participants were recruited purposefully and on a voluntary basis. Participants presented a case study about their approaches to implementing innovations between March-June 2020 and discussed their experiences and lessons learned. The focus groups were audio-recorded and transcribed verbatim. Transcripts and other documents were analyzed using qualitative thematic analysis following a combination of grounded theory and framework analysis approach. AHSNs increased the pace of their implementation work to support the response to the COVID-19 pandemic. The disruptive event changed the implementation context which enabled rapid implementation through an urgency for change, the need to adhere to social distancing rules, new enabling governance structures, and stakeholders' reduced risk averseness toward change. AHSNs achieved rapid implementation through: (1) An agile and adaptive implementation approach; (2) Accelerating existing innovations and building on existing relationships/networks; (3) Remote stakeholder engagement; and (4) Ensuring quality, safety, rigor and sustainability, and generating new evidence through rapid evaluations. AHSNs aimed at sustaining implementation pace and efficiency after the acute phase of the pandemic mainly through remote stakeholder engagement and flexibility of implementation strategies.